An aqueous garlic extract alleviates water avoidance stress-induced degeneration of the urinary bladder - (:unkn) unknown (WILEY, 2006)
OBJECTIVE To investigate the role of aqueous garlic extract (AGE) on the water-avoidance stress (WAS)-induced degeneration of the urinary bladder in a rat model. MATERIALS AND METHODS Wistar albino rats were exposed to WAS for 2 h/day for 5 days (WAS group), after which, AGE (1 mL/kg) was injected intraperitoneally into the rats (WAS + AGE group). Urinary bladder samples were investigated with both light and scanning electron microscopy, and lipid peroxidation and glutathion levels were also measured in the samples: RESULTS In the WAS group there was inflammatory cell infiltration, more mast cells and ulcerated areas in the mucosa. In the WAS + AGE group there was relatively normal urothelial alignment, moderate inflammatory cell infiltration and fewer mast cells in the mucosa. The increased lipid peroxidation and decreased glutathione levels in WAS rats were reversed by AGE treatment. CONCLUSIONS These results show that AGE has a protective effect on WAS-induced degenerative changes in the urinary bladder.
Keywords: water avoidance stress; aqueous garlic extract; interstitial cystitis; mast cell; microscopy; MAST-CELLS; ACTIVATION; PREVENTION; DAMAGE